Diversity of Fish in Idanoi River and It’s Relationship to Physical Factors of Water Chemistry - Ternala Alexander Barus (International Journal of Ecophysiology, 2021)
A river is an area through which a body of water moves from a high place to a low place either through the surface or underground which has an average width equal to or more than 5 meters. One of the rivers in Indonesia is the Idanoi river, located in the North Sumatra region, Ononamolo 1 Lot village, Gunungsitoli Selatan sub-district, Nias. This river is inseparable from human activities which affects the condition of river waters as a habitat for aquatic biota. The purpose of this study was to analyze the diversity of fish species in the river Idanoi and to analyze the physical-chemical factors of waters which correlate with the diversity of fish species in the river Idanoi. This study uses the Random sampling method. The results of the research obtained from the four research stations found 1 class, 5 orders, 7 families and 7 species. The highest density value was found at station 1 with a value of 0.023 ind / m2, fish diversity index ranged from 1.072 - 1.829 and the fish uniformity index ranged from 0.92 to 0.98. DO, BOD5 values and oxygen saturation correlated very strongly with fish diversity in river Idanoi village Ononamolo 1 Lot.